Efektifitas Posisi Meneran Semi-Fowler Dengan Posisi Berbaring Miring Ke Kiri Terhadap Kejadian Ruptur Perinieum Di Puskesmas Poned Jayakerta : The Effectiveness of the Semi-Fowler Pressing Position with Left Side Lying Position for Perineal Rupture at the Poned Jayakerta Health Center - Kartika, Eka; Feva Tridiyawati (Dohara POAJ, 2023)
Introduction: Perineal rupture occurs in almost all deliveries causing bleeding and infection, if not treated immediately it can cause death. One effort to reduce the occurrence of perineal rupture is the pressing position. Poned Jayakerta Health Center Karawang Regency in 2020 it was found that 66,8% had a perineal rupture, in 2021 it was found that 64,7% had a perineal rupture. When giving birth, the position that is often used is the semi-fowler and side-lying position. Methods: This research is quantitative analytic research with a post-test-only design with control groups. The sample in this study were mothers giving birth at the Poned Jayakerta Health Center Karawang Regency totaling 30 respondents with a total sampling technique. The research instrument uses an observation sheet. The data is primary data analyzed using the Mann-Whitney test. Results: The results of univariate analysis of the incidence of perineal rupture in the semi-fowler pressing position group with an average = 0,93; the incidence of perineal rupture in the supine position lying on its side with an average = 1,67. There is an effectiveness of the semi-fowler pressing position with a side-lying position on the incidence of perineal rupture with a p-value = 0,009. Discussion: The semi-fowler pressing position is more effective than the side-lying position in reducing the incidence of perineal rupture. Mothers in labor are expected to cooperate with midwives when facing the 2nd stage of labor so that mothers can follow guidance and direction from midwives when carrying out the pressing position and are able to press properly which has an impact on reducing the incidence of perineal rupture.